3. Buddhist Technologies of Statecraft and Millennial Moments - Blackburn, Anne M. (History and theory, 2017)
There are striking family resemblances between models and modes of kingship in the Safavid and Mughal worlds discussed by Azfar Moin and those that characterized Buddhist kingship in the premodern Indian Ocean arena, which encompassed polities including Poḷonnāruva, Dambadeṇiya, Koṭṭē, Bagan, Sukhothai, and Chiang Mai. In courtly contexts, Buddhists—operating at the intersection of intellectual traditions in Pali and Sanskrit languages—depended upon protective technologies including astrology and interpreted threats and prospects according to millennial science. Working comparatively, across the premodern Indian Ocean and Indo-Persian worlds, can help historians of Buddhism and Islam to understand more clearly the intellectual histories and repertoires of royal practice according to which kings and strongmen within each sphere sought to gain and retain the throne.